Diasporas engaging during the pandemic: international global exchanges in response to the Covid-19 crisis - Lara-Guerrero, Larisa (HAPSc Policy Briefs Series, 2020)
The Covid-19 pandemic is an unprecedented phenomenon that has challenged governments, international organisations, academics, and members of the civil society worldwide. In an effort to contribute to the alleviation of the pandemic and enhance the dialogue among diaspora experts, the International Organisation of Migration and iDiaspora organised three global exchanges. This policy brief argues that these platforms are particularly useful in times of crisis and restricted mobility because diasporas around the world have been able to share crucial information, give advice and create an open dialogue to inspire other migrants to develop their own initiatives against the pandemic.